Clinico-dermoscopic evaluation of cervico-facial melanosis with histopathological correlation - Davuluri, Monica; Yadalla, Harikishan Kumar; Shivappa, Naveen; Samagani, Akshay (International Journal of Research in Dermatology, 2025)
Background: Cervico-facial melanosis, due to their visibility are a frequent cause of dermatologic consultation causing significant cosmetic and psychosocial burden. For successful treatment, diagnosis of the facial melanosis is important. Combining different modalities like dermoscopy and histopathology helps in better management of these disorders. Aim of the study was to study the clinical profile of cervico-facial melanosis and evaluate them with a dermoscope and to correlate histopathological findings with clinical and dermoscopic findings. Methods: Study was conducted from July 2022 to December 2023. 50 patients suffering from cervico-facial hypermelanosis were enrolled. Complete clinical evaluation with detailed history and physical examination was done. All patients underwent skin biopsy and dermoscopic evaluation. Results: In the present study all patients fulfilling the inclusion and exclusion criteria and willing for biopsy were only enrolled, the most common diagnosis being lichen planus-pigmentosus (LPP) in 18(36%) patients, ashy dermatosis (AD) in 15(30%), postinflammatory hyperpigmentation (PIH) in 6(12%), acanthosis nigricans (AN) in 4 (8%), Riehls melanosis (RM) in 3 (6%), melasma in 2 (4%), nevus of ota (NOO) in 1 (2%), macular amyloidosis (MA) in 1 (2%) patient. Conclusions: Hyperpigmentary disorders have often shown that Clinical examination alone can misdiagnose certain conditions. Hence this study reinforces that the dermoscope proves to be a valuable tool in diagnosis, prognosis, and follow up of disorders of cervico-facial hyperpigmentation in conjunction with HPE for confirmation and effective management of these cases.